Heat Capacity and Thermodynamic Functions of Sr(La1-xLnx)2WO7 Compounds Doped with Samarium and Europium - Sadyrbekov, D.T.; Bissengaliyeva, M.R.; Gogol, D.B.; Bekturganov, N.S.; Taimassova, S.T. (Eurasian Chemico-Technological Journal, 2021)
Samples based on strontium, lanthanum and tungsten with the general formula of Sr(La1-xLnx)2WO7 doped with samarium and europium at 1 and 3 at.% were synthesized by the solid-phase method at temperatures up to 1200 °C. The crystal structure of the samples was confirmed by X-ray powder diffraction. A full-profile refinement of the structure of compounds related to monoclinic syngony with the space group P1121/b was performed. The admixture phase is a compound of the Sr3Ln2W2O12 type with a trigonal system and space group R3c. Based on the results of structure refinement, the ratio of the main compound and the admixture phase in the samples was determined to introduce corrections during measurements. Using adiabatic calorimetry we measured the heat capacity of the samples and found the thermodynamic functions of main compounds over the range of 5‒320 K. Anomalies were detected in the heat capacity of the samples below 15 K, and we calculated the excess and lattice heat capacity for these anomalies by means of linearization methods.
Keywords: Lanthanum; Samarium; Europium; Tungsten; Ternary oxide; XRD; Adiabatic calorimetry